2013
DOI: 10.1093/jnci/djt022
|View full text |Cite
|
Sign up to set email alerts
|

A Cancer Stem Cell Model for Studying Brain Metastases From Primary Lung Cancer

Abstract: For the first time, we demonstrate the presence of a stemlike population in brain metastases from the lung. We also show that NCI-H1915 tumorspheres could be useful in studying self-renewal and tumor initiation in brain metastases. Our candidate genes may be essential to metastatic stem cell populations, where pathway interference may be able to transform a uniformly fatal disease into a more localized and treatable one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 68 publications
2
55
0
Order By: Relevance
“…We also performed a traditional and reliable limiting dilution assay (LDA) to determine the fraction of CSCs in each subpopulation. The LDA results revealed the frequency of sphere formation, providing useful information for interpreting the composition of the mixed population of CSCs [23, 46]. Our current data showed that Lgr5-positive subpopulations possessed a higher percentage of CSCs than did Lgr5-negative subpopulations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We also performed a traditional and reliable limiting dilution assay (LDA) to determine the fraction of CSCs in each subpopulation. The LDA results revealed the frequency of sphere formation, providing useful information for interpreting the composition of the mixed population of CSCs [23, 46]. Our current data showed that Lgr5-positive subpopulations possessed a higher percentage of CSCs than did Lgr5-negative subpopulations.…”
Section: Discussionmentioning
confidence: 60%
“…The LDA and tumor sphere-forming assays were performed as previously described, with some modifications [23]. In brief, limiting dilutions of tumor cells were plated (4 to 0.5 cells per well) in 0.2 ml of serum-free DMEM/F12 medium as described for the sphere-forming assay and were cultured for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported the increased invasiveness of CSCs, implicating the involvement of CSCs in the progression and/or development of metastases (46,47). However, most previous in vitro drug screenings on lung cancer patient-derived cancer cells were performed in serum-containing medium (48), whereas tumor spheres in serum-free condition enrich CSC-like populations (49). Herein, PDXs derived from NSCLC brain metastases gave rise to numerous tumor spheres in a few days after mechanical dissociation ex vivo in a reproducible manner, whereas PDXs from NSCLC primary tumor demonstrated poor viability and sphereforming ability in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that these CSCs in lung cancer resist to chemotherapeutic agents and have high tumorigenic potential (12,70). Also, the lung CSCs were shown to have augmented ability to move to other tissues (8,12,71). The most important characteristic of CSCs is their ability to generate a new tumor.…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Several CSC makers have been used to identify the CSC population in lung cancer, including cellular expression of CD44, CD133 and CD166 (67)(68)(69)(70)(71). Also aldehyde dehydrogenase (ALDH) activity and expression have been shown to indicate stemness in lung cancer (67)(68)(69)(70)(71).…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%